Genomic data reveal international lineages of critical priority Escherichia coli harbouring wide resistome in Andean condors (Vultur gryphus Linnaeus, 1758). Issue 10 (31st May 2020) - Fuentes‐Castillo, Danny; Esposito, Fernanda; Cardoso, Brenda; Dalazen, Gislaine; Moura, Quézia; Fuga, Bruna; Fontana, Herrison; Cerdeira, Louise; Dropa, Milena; Rottmann, Jürgen; González‐Acuña, Daniel; Catão‐Dias, José L.; et al.
Abstract: Critical priority pathogens have globally disseminated beyond clinical settings, thereby threatening wildlife. Andean Condors ( Vultur gryphus ) are essential for ecosystem health and functioning, but their populations are globally near threatened and declining due to anthropogenic activities. During a microbiological and genomic surveillance study of critical priority antibiotic‐resistant pathogens, we identified pandemic lineages of multidrug‐resistant extended‐spectrum β‐lactamase (ESBL)‐producing Escherichia coli colonizing Andean Condors admitted at two wildlife rehabilitation centres in South America. Genomic analysis revealed the presence of genes encoding resistance to hospital and healthcare agents among international E. coli clones belonging to sequence types (STs) ST162, ST602, ST1196 and ST1485. In this regard, the resistome included genes conferring resistance to clinically important cephalosporins (i.e., CTX‐M‐14, CTX‐M‐55 and CTX‐M‐65 ESBL genes), heavy metals (arsenic, mercury, lead, cadmium, copper, silver), pesticides (glyphosate) and domestic/hospital disinfectants, suggesting a link with anthropogenic environmental pollution. On the other hand, the presence of virulence factors, including the astA gene associated with outbreak of childhood diarrhoea and extra‐intestinal disease in animals, was identified, whereas virulent behaviour was confirmed using the Galleria mellonella infection model. E. coli ST162, ST602, ST1196 and ST1485 have been previously identified in humans and food‐producing animals worldwide, indicating that a wide resistome could contribute to rapid adaptation and dissemination of these clones at the human–animal–environment interface. Therefore, these results highlight that Andean Condors have been colonized by critical priority pathogens, becoming potential environmental reservoirs and/or vectors for dissemination of virulent and antimicrobial‐resistant bacteria and/or their genes, in associated ecosystems and wildlife.